(untitled) (Research, Society and Development, 2020)
The lifestyle in the digital world signals changes in the professional, educational and social spheres. Digital technologies can contribute in several areas. Thus, using the knowledge construction process can generate a potential gain. This article indicates changes in the teaching and learning process, related to the insertion of digital technologies and the teaching and learning strategy used. This literature review aims to raise awareness of studies published between 2015 and 2019 related to the support of digital technologies to the Problem Based Learning (PBL) strategy. As a methodological characteristic, it refers to an exploratory study of a qualitative nature. For the methodology, the search criteria of the Scopus, Eric and Web of Science indexers were used, with keywords related to PBL strategies and as digital technologies, followed by exclusion and selection of available articles. The articles present practical studies involving the theme, which resulted in challenges and benefits in the educational field. Through the analysis of the studies it was possible to verify that the use of digital technologies provided, in general, interaction, knowledge and digital skills. The advances pointed out improvement indications future implementations, considering a better performance of all accomplished.